Navigation Sonar: More Than Underwater Radar — Realizing the full potential of navigation and obstacle avoidance sonar - Russel, Ian; Wright, R. Glenn (The International Hydrographic Review, 2017)
At least half the world’s coastal waterways are inadequately surveyed or not surveyed at all. Coverage is particularly poor in the Caribbean, the Indian and Pacific Oceans and the Polar regions. Recent accounts of vessels grounding on uncharted seabed features reflect this situation. Advances in three dimensional (3D) Navigation Sonar that can reduce vessel risk in such areas are described. This technology has the potential to enhance the safety of navigation for vessels and for those that follow in their wake. New generations of coastal trading vessels, cruise and adventure ships together with a variety of government vessels can all benefit from this technology.